Research on Value Assessment and Compensation for Health Hazards of Urban Air Pollution-A Case Study of Urumqi - Yu,Chen (2016)
ABSTRACT With the acceleration of urbanization and industrialization, urban air pollution has become a serious threat to the health of urban residents. In this study, to investigate health hazards caused by air pollution for urban residents, concentrations of main air pollutants and annual coal consumption amounts during the period from 2000 to 2013 were analyzed. Our results showed that economic losses of Urumqi caused by air pollution amounted to 63.155 million yuan in 2013, accounting for 0.2 ‰ of its GDP and 5.7% of public utility expenditures for that year. The compensation mechanism analysis suggested that it is necessary to further improve the health care system and increase corporate environmental taxes. More environmental health protection taxes should be levied on key monitoredenterprises in Urumqi to achieve effective compensations for urban residents affected by air pollution-related health hazards.